Low sensitivity of a test for anti‐Mullerian hormone to assess presence of ovaries in prepubertal bitches. Issue 9 (27th August 2018) - Hill, JR; Wilkinson, J; Mallyon, J; Anderson, ST
Abstract : Background: Anti‐Mullerian hormone (AMH) is currently used in several species as an indicator of the number of antral and pre‐antral follicles within the ovaries. Currently, there is some uncertainty on the precision of a single AMH test for detecting the presence of ovarian tissue in prepubertal, pubertal and spayed bitches. The purpose of this study was to investigate the specificity of AMH levels determined using the Gen II AMH ELISA to detect the presence or absence of ovarian tissue in bitches of varying ages. Methods: From a large cohort of dogs located at an animal shelter, 36 bitches were assigned to three age groups (< 6 months; 6–18 months and > 2 years of age) plus a group of six spayed bitches. Results: AMH was below the detectable limit for each spayed bitch (< 0.010 ng/mL) and for 9/10 intact bitches aged less than 6 months. AMH levels were therefore significantly different for these two groups compared with older intact bitches (6–18 months, 0.302 ± 0.135 ng/mL; > 2 years, 0.237 ± 0.210 ng/mL). AMH was undetectable in two intact bitches aged > 2 years of age, which gave a sensitivity of 82% in that group. Overall, the sensitivity of the test was 90% for all bitches aged over 6 months, which highlights that a small percentage of intact females will be incorrectly diagnosed as having no ovarian tissue. Conclusion: AMH testing had very low sensitivity in bitches aged less than 6 months and thus it is advisable to delay testing in very young bitches.